Educational Case: Endocrine Neoplasm - Sheila Segura MD; Gloria Ramos-Rivera MD; Mark Suhrland MD (Elsevier, 2018)
Medullary thyroid cancer is a rare neuroendocrine tumor that arises the neural crest-derived parafollicular C cells and accounts for approximately 5% to 10% of thyroid cancers worldwide. These tumor can occur sporadically or as part of hereditary tumor syndromes, such as multiple endocrine neoplasia 2 and familial medullary thyroid cancer. The most common clinical presentation is a solitary thyroid nodule. The genetic defect in these disorders involves the RET proto-oncogene which is important for diagnosis of medullary thyroid cancer (including screening for hereditary medullary thyroid cancer) and for treatment guidance. This review summarizes the molecular basis and clinicopathologic features of medullary thyroid carcinoma.